Global Food Price Inflation : Implications for South Asia, Policy Reactions, and Future Challenges - Ahmed, Sadiq (Washington, DC: World Bank, 2012)
The surge in global commodity prices of the past few years has presented a tremendous development challenge for South Asian countries. The large loss of income from the terms of trade shock has worsened macroeconomic balances, fueled rapid inflation, and hurt growth. Although commodity prices have come down recently, the benefits are being clouded by the emergence of a severe global financial crisis. The adverse consequences of the food price hike for the poor are large; the global financial crisis could further worsen the situation due to falling economic opportunities and government revenues. South Asian countries need to accelerate reforms to avoid facing a serious downturn in economic activity, investment, exports, and income. Governments in South Asia have responded by stabilizing domestic food prices through a number of short-term measures, tightened monetary policy to reduce inflation, and increased spending on a range of safety net programs for the poor. Some of the policies employed, such as export bans, are not consistent with the long-term welfare of the country or the region. Safety net interventions need to be made consistent with a longer-term poverty reduction strategy and fiscal sustainability. Most importantly, policy attention now needs to shift toward efforts to increase farm productivity, improve rural infrastructure, and lower the vulnerability of the poor.